Predicting postoperative complications after pediatric perforated appendicitis - Frongia, Giovanni; Mehrabi, Arianeb; Ziebell, L.; Schenk, Jens-Peter; Günther, Patrick (Journal of investigative surgery, 2016)
Purpose: Assessment of risk factors for postoperative complications following surgical treatment of pediatric perforated appendicitis (PA) is necessary to identify those patients in need of closer monitoring. In this study, we have investigated the impact of different risk factors on the occurrence of complications after an appendectomy in children with PA. Material and Methods: The study was a retrospective, single-centre analysis of all pediatric PA conducted over a 10-year period. Preoperative clinical and laboratory results, intraoperative findings, and postoperative complications were analyzed. Risk factors were defined and a risk score was determined for postoperative complications and reinterventions. Results: Surgical treatment for appendicitis was performed in 840 pediatric patients during the observation period. 163 of the included patients were diagnosed with PA (mean age 8.9 ± 3.6 years). 19 (11.7%) patients developed postoperative complications, 17 (10.4%) of which required complication-related intervention. We identified five predictors of postoperative complications: the C-related protein value at admission, purulent peritonitis, open appendectomy (primary, secondary, or converted), placement of an abdominal drain, and administration of antibiotics not compliant to results from the subsequent antibiogram. The determined risk score was significantly higher in the complication group (p < .0001) and reintervention group (p < .001). Conclusions: Postoperative complications following pediatric PA can be predicted using specific preoperative, intraoperative, and postoperative risk factors. In the high-risk group, an active prevention, detection, and intervention of any occurring complication is necessary and we present a new specific pediatric risk score to define patients at risk for complications.